2018
DOI: 10.1002/gcc.22699
|View full text |Cite
|
Sign up to set email alerts
|

An update of molecular pathology of bone tumors. Lessons learned from investigating samples by next generation sequencing

Abstract: The last decade has seen the majority of primary bone tumor subtypes become defined by molecular genetic alteration. Examples include giant cell tumour of bone (H3F3A p.G34W), chondroblastoma (H3F3B p.K36M), mesenchymal chondrosarcoma (HEY1‐NCOA2), chondromyxoid fibroma (GRM1 rearrangements), aneurysmal bone cyst (USP6 rearrangements), osteoblastoma/osteoid osteoma (FOS/FOSB rearrangements), and synovial chondromatosis (FN1‐ACVR2A and ACVR2A‐FN1). All such alterations are mutually exclusive. Many of these have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 90 publications
(194 reference statements)
1
56
0
6
Order By: Relevance
“…However, depending on the developmental timing of the derivation of a bone cancer from the mesenchymal lineage during embryonal or adult osteogenesis, these roles may vary. Chordoma localized along the skeletal axis in bones from the skull base to the coccyx is considered to derive from early developmental mesodermal cell types in notochord remnants [164]. Chondrosarcoma, the most common malignant bone tumor in adults, is considered to derive from benign enchondroma or osteochondroma, which are thought to arise from rests of growth plate cartilage or chondrocytes [165].…”
Section: Yap and Taz As Regulators Of Osteogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the developmental timing of the derivation of a bone cancer from the mesenchymal lineage during embryonal or adult osteogenesis, these roles may vary. Chordoma localized along the skeletal axis in bones from the skull base to the coccyx is considered to derive from early developmental mesodermal cell types in notochord remnants [164]. Chondrosarcoma, the most common malignant bone tumor in adults, is considered to derive from benign enchondroma or osteochondroma, which are thought to arise from rests of growth plate cartilage or chondrocytes [165].…”
Section: Yap and Taz As Regulators Of Osteogenesismentioning
confidence: 99%
“…For osteosarcoma, there is evidence for derivation from pre-osteoblasts or osteoblasts with the contribution of microenvironmental mesenchymal stem cells (MSC) (for review, [173,174]). Similarly, a giant cell tumor of bone, a rare, locally aggressive tumor which occasionally metastasizes to the lung, is of osteoblastic lineage [164].…”
Section: Yap and Taz As Regulators Of Osteogenesismentioning
confidence: 99%
“…In 1999, Panoutsakopoulos et al demonstrated a balanced chromosomal translocation t(16; 17)(q22;p13) as a cytogenetic abnormality in primary aneurysmal bone cyst [7] involving the ubiquitin carboxylterminal hydrolase 6 (USP6) gene, located on chromosome 17p13. Since then, the neoplastic nature of ABC has been established and the USP6 translocation has since been found in approximately 75% of cases [8]. In differentiating primary ABC's from secondary lesions or other tumors such as telangiectatic osteosarcoma this may be an option in selected cases.…”
Section: Introductionmentioning
confidence: 99%
“…bone tumors. Based on these findings, molecular testing as well as specific immunohistochemistry has found its way in routine bone tumor diagnostics that historically heavily relied on morphology and has improved diagnostic accuracy [4,5]. Recently, recurrent translocations in FOS (87%) and FOSB (3%) were found in osteoblastoma and osteoid osteoma [6].…”
Section: Introductionmentioning
confidence: 99%